2015
DOI: 10.3945/ajcn.115.112581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low- and high-carbohydrate diets for type 2 diabetes management: a randomized trial

Abstract: Both diets achieved substantial weight loss and reduced HbA1c and fasting glucose. The LC diet, which was high in unsaturated fat and low in saturated fat, achieved greater improvements in the lipid profile, blood glucose stability, and reductions in diabetes medication requirements, suggesting an effective strategy for the optimization of T2D management. This trial was registered at www.anzctr.org.au as ACTRN12612000369820.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
310
4
23

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(358 citation statements)
references
References 55 publications
21
310
4
23
Order By: Relevance
“…Part of the confusion is due to the wide range of definitions for a low-carbohydrate diet (73,74). While benefits to low-carbohydrate diets have been described, improvements tend to be in the short term and, over time, these effects are not maintained (74)(75)(76)(77). While some studies have shown modest benefits of very low-carbohydrate or ketogenic diets (less than 50-g carbohydrate per day) (78,79), this approach may only be appropriate for short-term implementation (up to 3-4 months) if desired by the patient, as there is little longterm research citing benefits or harm.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Part of the confusion is due to the wide range of definitions for a low-carbohydrate diet (73,74). While benefits to low-carbohydrate diets have been described, improvements tend to be in the short term and, over time, these effects are not maintained (74)(75)(76)(77). While some studies have shown modest benefits of very low-carbohydrate or ketogenic diets (less than 50-g carbohydrate per day) (78,79), this approach may only be appropriate for short-term implementation (up to 3-4 months) if desired by the patient, as there is little longterm research citing benefits or harm.…”
Section: Carbohydratesmentioning
confidence: 99%
“…In addition, these diets have been shown with highest quality and clinically relevant research methods to work better than the more traditional higher-carbohydrate, higher-fiber diets for metabolic conditions like diabetes, heart disease [34][35][36][37][38][39][40][41][42] (Figure). Expanding lifestyle modifications for increasing microbiota diversity, recommendation is to connect with nature like walking in a forest or by the sea.…”
Section: How To Create a Healthy Environment For A Healthy Microbiotamentioning
confidence: 99%
“…43 Recently, Tay et al reported on a randomized controlled study investigating hypocaloric low carbohydrate versus high carbohydrate diets over 24 weeks and 1 year, respectively, in obese adults with T2DM. 44,45 Saturated fat intake was limited to ,10% despite total fat intake being 58% and carbohydrate 14% of the total energy intake in the low carbohydrate group. Intensive dietary counseling and a physical activity plan were included.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Tay et al demonstrated that maintaining saturated fat to the recommended level below 10% prevents increases in LDL cholesterol seen with traditional low carbohydrate high fat diets. 45 Intensive dietary counseling was required to sustain the study diets but this study suggests that VLCD's may be possible in T2DM without worsening cardiovascular risk. Some of these factors are present in the "paleolithic diet", which is discussed later.…”
mentioning
confidence: 93%